2018
DOI: 10.1001/jama.2018.8194
|View full text |Cite
|
Sign up to set email alerts
|

Annual Risk of Major Bleeding Among Persons Without Cardiovascular Disease Not Receiving Antiplatelet Therapy

Abstract: A decision to initiate aspirin therapy for primary prevention of cardiovascular disease (CVD) requires consideration of both treatment benefits and harms. The most significant harm associated with aspirin is major bleeding, yet there is a paucity of data on bleeding risk in suitable community populations. OBJECTIVE To determine the risk of major bleeding among people without CVD who are not receiving antiplatelet therapy. DESIGN, SETTING, AND PARTICIPANTS Prospective cohort study of 359 166 individuals aged 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 22 publications
6
30
1
1
Order By: Relevance
“…person-years, which was similar to findings in the present study. 24 A review of studies from Europe on acute upper GIB that used data from the 1990s reported that the incidence rate of acute upper GIB ranged from 0.36 to 1.72 per 1000 person-years, 13 which was within or higher than the range shown in the present study. Compared with the present study, the incidence rates of upper GIB in the United States (from 1998 to 2006) were higher at between 1.46 and 1.70 per 1000 person-years and were comparable to those of Spain (from 1996 to 2005), which ranged from 0.47 to 0.87 per 1000 person-years.…”
Section: Discussionsupporting
confidence: 40%
“…person-years, which was similar to findings in the present study. 24 A review of studies from Europe on acute upper GIB that used data from the 1990s reported that the incidence rate of acute upper GIB ranged from 0.36 to 1.72 per 1000 person-years, 13 which was within or higher than the range shown in the present study. Compared with the present study, the incidence rates of upper GIB in the United States (from 1998 to 2006) were higher at between 1.46 and 1.70 per 1000 person-years and were comparable to those of Spain (from 1996 to 2005), which ranged from 0.47 to 0.87 per 1000 person-years.…”
Section: Discussionsupporting
confidence: 40%
“…atrial fibrillation) in older adults may account for this finding. A cohort study has shown that the risk for bleeding, especially gastrointestinal bleeding, inherently increases with rising age [60], it may then be potentiated by antithrombotics. In this respect, higher numbers of ADR reports with regard to gastrointestinal and nervous system haemorrhages associated with direct oral anticoagulants have been seen in patients aged 60 years or older compared to younger patients in a study performed in two large ADR databases from USA and Japan [61].…”
Section: Discussionmentioning
confidence: 99%
“…First, Brunetti and Bo argue that "major bleeding incidences observed in DOAC experimental and observational studies are quite reassuring", thereby referring to major bleeding rates (1.6%-2.3% per year) among elderly individuals not receiving antithrombotic therapies. 3 We agree that major bleeding is a multicausal disease and that DOACs are not the only factor that can induce bleeding. Still DOACs have, like all anticoagulants, the side effect of bleeding, as for instance has been shown in placebo-controlled trials in which the risk of major or clinically relevant bleeding is elevated for DOAC use.…”
Section: The Relationship Between Doac Levels and Clinical Outcomes: mentioning
confidence: 82%